Community Interpreting and linguistics: A fruitful alliance? A survey of linguistics-based research in CI - Valero Garcés, Carmen (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Since the first Critical Link Conference in Geneva Park, Canada, in 1995, Community Interpreting (CI) has experienced a dramatic change in both theory and practice. National and international conferences, seminars, courses, and workshops all around the world have made it possible for practitioners, trainers, and researchers to get together and discuss their views and exchange ideas. At the same time, an ever-growingflow ofpublications reflects the enormous activity in this field. Nevertheless, CI re- search is still farfrom being in the same category as infields such as conference interpreting or translation, and this is all the more so for linguistics-based CI research.As a researcher working in a department mostly involved with linguistics and related areas but with an increasing interest in cultural studies and translation studies, it is my intention to analyze and classify the contributions to CI conferences and the publications of CI papers using a linguistics-based methodology. To begin with, the evolution of linguistics and those sub-areas, which have had the greatest influence in the lastfew decades, will be briefly discussed, as will its methodologies. Secondly, an analysis will be presented of the characteristics and tools of linguistics-based CI research. And thirdly, conclusions will be drawn concerning the evolution, trends or gaps in CI research in general, and in linguistics-based CI research in particular.